Peran Insulin-like Growth Factor-1 (IGF-1) terhadap Penyakit Kardiovaskular - Fitrianisa Faradina Zubadi; Herpan Harahap; Legis Saputri; Arina Windri Rivarti (Lombok Medical Journal, 2024)
Insulin-like growth factor 1 (IGF-1) is a major regulator of somatic growth that mediates the effects of growth hormone (GH). IGF-1 receptors are expressed by three major cells involved in the pathogenesis of atherosclerosis, namely endothelial cells, macrophages, and smooth muscle cells. Recent in vivo studies have discussed the effects of IGF-1 on the pathogenesis of atherosclerosis. This paper will discuss the relationship and role of IGF-1 in heart and blood vessel disease.